Encyclopedia of radicals in chemistry, biology, and materials - Chatgilialoglu, Chryssostomos; Studer, Armido (Chichester, UK. : John Wiley & Sons, 2012)
'In recent years, free radicals have played an important role in various disciplines, ranging from organic synthesis to biology and medicine, polymer chemistry and materials science. The aim of this handbook is to offer for the first time a description of free radicals within an interdisciplinary and multidisciplinary context, connecting structural characteristics and chemical properties to their applications in different areas of chemistry and related disciplines. The Handbook covers not only basic concepts and chemical synthesis, but also touches on various aspects concerning the role of free radicals in materials and life sciences. The reader will find a balanced contribution of topics related to free radicals covering for example, their role in proteomics, genomics and lipidomics as well as their enormous potential in synthesis and technology. The Handbook will be interesting for anybody working in the field of free radicals in the broadest sense. It will address scientists who want to enter the interdisciplinary field of free radicals. In particular, it is aimed primarily at chemists and life science researchers who want to gain a wider and deeper understanding of free radicals which will allow them to apply free radicals in their own scientific field. The book consists of four themed volumes: Basic Concepts & Methodologies, Synthetic Strategies & Applications, Chemical Biology, Polymers & Materials. Within the volumes the chapters will also be thematically structured'--
v.1. Basic concepts and methodologies -- v. 2. Synthetic strategies and applications -- v. 3. Chemical biology -- v. t4. Polymers and materials.
Includes bibliographical references and indexes.
Keywords: Free radicals (Chemistry).; Radicals (Chemistry).